Design of a Teleworking Service Using Parlay Framework Federation - Amilcar, Akin-Ojo (My University, 2006)
A teleworking service allows people to work effectively together from home or other approved locations away from the regular work site, on an established work schedule. This is made possible via the use of Information and Communications Technology (ICT). Presently, there are isolated applications that can assist teleworkers, such as e-mail and video conferencing, which were developed for use over the Internet. But the Internet is a best-effort network with no guarantee of Quality of service (QoS), low security and no standard billing system. The design of this teleworking service involves the integration of many existing services like e-mail, messaging, video conferencing, shared whiteboard and database access. Other requirements are for service providers interworking for service and resource usage, security, and QoS specification. Hence, we explore the emerging open service concept to create this integrated teleworking service that can be made available for subscription by corporate bodies and individuals. Service federation is the interaction between teleworkers across service provider domains. It is achieved via the interworking of providers’ services, and is an essential aspect of teleworking. We have realised a service federation in a secure and seamless manner in the OSA / Parlay environment via the use of the OSA / Parlay framework. We looked at the use of a framework federation for the actual implementation of service federation. This framework federation is an interworking of frameworks based on an agreed-upon federation contract between them. New framework interfaces were introduced to facilitate this proposed solution, as the OSA / Parlay specifications do not yet support this approach. Service composition is the creation of a new service instance by composing one or more other services. We implemented this via the use of framework and trader federation. The trader federation was used to locate services or users in different ASP domains. A high level design of the teleworking service was done with federation explored for actual implementation. The Common Object Request Broker Architecture (CORBA) trading service was used to prove the concept. The RM-ODP methodology is followed in this teleworking service design. The OSA / Parlay terminal capability, generic call control, multiparty and location and Service Capability Features (SCF) were used for implementing in the CORBA Distributed Processing Environment (DPE).
Faculty of Engineering and Built Enviroment School of Electrical and Information Engineering 0314356t morayus@engineer.com
Keywords: Teleworking; SCF; DPE